FACTORS RELATED TO EMPLOYEE SATISFACTION IN THE HOSPITAL PUBLIC SERVICE AGENCY OF KONAWE DISTRICT: Employee Satisfaction - Alisia Witanti; La Ode Saafi; La Ode Kamalia (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2021)
Background:The increasing of number of patient visits every year and the ratio of bed usege must be comparable to satisfied employees. However, this has not been in line with the satisfaction felt by employees at the Konawe District Hospital. The purpose of this research is to learn factors related to employee satisfaction at the Regional Uum Service Agency Regional General Hospital, Konawe Regency Hospital. Methods: The study was a quantitative study using a cross sectional study design.The population in this study were all employees at the Bombana District Hospital,namely 157 people. The number of samples in this study were 210 people. The sample was determined by simple random sampling technique. The data were processed using thechi square test. Result: The results of the study using the chi square test show that management is significant towards employee satisfaction (X2cal. . = 33,925> X2tab =3,841), education and training are significant to employee satisfaction (X2 cal.  = 39,230> X2tab =3,841. Conclusion: Management is related to employee satisfaction and education. training is also related to employee satisfaction at Konawe District Hospital. However, reward is not related to employee satisfaction.